Female Leadership Style At Lkp Mayang Sari In Bengkulu City In Improving Employee Performance - IS, Tuti Handayani; Imanda, Antonio; Sapruzi, Gaul (Journal of Research in Social Science and Humanities, 2021)
This study aims to describe the female leadership style in improving employee performance at LKP Mayang Sari, Bengkulu City. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation involving the institution's leader and employees. The results reveal that the female leader effectively carries out interpersonal, decision-making, and informational roles. Her leadership style emphasizes discipline, role modeling, empathy, and motivation, all of which positively affect employee performance. Despite occasional challenges in decision-making—often influenced by emotion—the female leader demonstrates professionalism in leading the institution. The study suggests that female leadership can significantly contribute to organizational growth when supported by strong interpersonal competencies. These findings are expected to contribute to the development of public administration science, particularly in gender-based leadership studies.